Oxygen-assisted stabilization of single-atom Au during photocatalytic hydrogen evolution - Zeng, Lei (2020)
Pre-treatment of graphitic carbon nitride (GCN) with H2O2 introduces active C–OH groups that can react with HAuCl4 to immobilize single atom Au(I) in the GCN matrix through creating robust Au(I)–O coordination bonds. This strong bonding can effectively restrict the diffusion of intermediate Au(0) towards the formation of Au particles during the photocatalytic hydrogen evolution process. As such, the single atom Au(I) incorporated GCN maintained superior activities with excellent stabilities for photocatalytic hydrogen generation.